Nonlinear circuit simulation and modeling fundamentals for microwave design - Pedro, José Carlos 1962-; Root, David E.; Xu, Jianjun; Nunes, Luís Cótimos (The Cambridge RF and microwave engineering series, 2018)
Discover the nonlinear methods and tools needed to design real-world microwave circuits with this tutorial guide. Balancing theoretical background with practical tools and applications, it covers everything from the basic properties of nonlinear systems such as gain compression, intermodulation and harmonic distortion, to nonlinear circuit analysis and simulation algorithms, and state-of-the-art equivalent circuit and behavioral modeling techniques. Model formulations discussed in detail include time-domain transistor compact models and frequency-domain linear and nonlinear scattering models. Learn how to apply these tools to designing real circuits with the help of a power amplifier design example, which covers all stages from active device model extraction and the selection of bias and terminations, through to performance verification. Realistic examples, illustrative insights and clearly conveyed mathematical formalism make this an essential learning aid for both professionals working in microwave and RF engineering and graduate students looking for a hands-on guide to microwave circuit design